Soil database for development of soil properties envelope - Satyanaga, Alfrendo (2022)
Residual soils are commonly found in unsaturated condition, and they are associated with high variability. It is necessary to develop a soil database for simplicity of geotechnical analyses and design with respect to cost optimization. This study focused on developing a framework for creating a soil database based on boreholes from different projects, locations and time in Singapore. The soil database was developed utilizing user-friendly and low-cost platforms, i.e. Microsoft Access and Visual Basic Application (VBA). The developed soil database was used to generate saturated and unsaturated soil properties envelopes in Singapore. The developed soil properties envelopes were evaluated by the results from experimental works in this study. The five-parameter logistic curve was chosen as the best-fitting function to develop envelopes with reference to the boxplot. The analyses indicated that soils located at deeper depths have lesser percentage of fine particles which results in a higher saturated permeability, effective friction angle and unsaturated ϕb angle. The results from statistical analyses indicate certain upper limit, typical and lower limit for air-entry value (AEV) for residual soils from Jurong Formation, Bukit Timah Granite and Old Alluvium. Residual soils from each formation located at the ground surface produced the highest AEV while soils at deeper depths exhibit a lower AEV.